2021
DOI: 10.1080/13880209.2021.2017981
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Huangqin decoction on regulating intestinal flora in colitis mice characterized as inhibition of the NOD2-dependent pathway

Abstract: Context Chinese herb Huangqin decoction (HQD) can regulate intestinal flora in ulcerative colitis (UC) mice. Objective Our study clarifies the mechanism of HQD in regulating the intestinal flora of UC mice. Materials and methods Male C57BL/6 mice were randomly divided into six groups: Control, Model (3% DSS), Sulfasalazine (500 mg/kg), HQD-L (250 mg/kg), HQD-M (500 mg/kg), and HQD-H (1000 mg/kg) groups. Measurement of body weight, colon lengt… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 20 publications
1
6
0
Order By: Relevance
“…Furthermore, Clostridium was enriched after HQD treatment along with higher levels of the three major SCFAs. Previous study has also proved the effect of HQD in reversing intestinal flora dysbiosis in colitis model [27]. Our finding revalidated this ability of HQD in the CRC model, reflecting the TCM characteristics of the same treatment for different diseases.…”
Section: Revealing the Hqd Mechanism In Crc: The Microbiome Viewsupporting
confidence: 75%
See 1 more Smart Citation
“…Furthermore, Clostridium was enriched after HQD treatment along with higher levels of the three major SCFAs. Previous study has also proved the effect of HQD in reversing intestinal flora dysbiosis in colitis model [27]. Our finding revalidated this ability of HQD in the CRC model, reflecting the TCM characteristics of the same treatment for different diseases.…”
Section: Revealing the Hqd Mechanism In Crc: The Microbiome Viewsupporting
confidence: 75%
“…These granules were boiled in distilled water for 3 min and stored at 4 °C for 1 week. Extraction and quality-control assessment of the ingredients in HQD has been previously reported [27], in which paeoniflorin, glycyrrhizic acid, baicalin, wogonoside and liquiritin are the top active constituents with high concentrations.…”
Section: Methodsmentioning
confidence: 99%
“…Here, we further observed that similar to mesalazine, HQD exhibited an antitumor effect on mice induced with CAC. Although HQD has been shown to effectively inhibit DSS-induced colitis alone or by synergizing with Radix Actinidiae chinensis , this main function was associated with altering the composition of the intestinal flora and modifying the proportion of T-cell subsets in colorectal lymphoid tissues (Huang et al 2022a , b ). Therefore, the immunoregulatory function of HQD needs to be further explored and verified.…”
Section: Discussionmentioning
confidence: 99%
“…Huangqin Decoction could reduce the abundance of deferribacteraceae, deferribacteres, alcaligenaceae, and the pathogenic bacteria, and restore gut microbiota diversity in DSS-induced colitis [ 43 ]. Huangqin Decoction has also been shown to increase the relative abundance of Proteobacteria and Firmicutes at the phylum level, while decreasing the abundance of bacteroides, escherichia-shigella, parabacteroides, and ruminococcus torques, and increasing the abundance of blautia, lachnospiraceae NK4A136 group, rikenella, and C. leptum at the genus level [ 44 ].…”
Section: Compound Tcm Prescriptions For the Uc Treatmentmentioning
confidence: 99%